Gendered Authority in Traditional Justice Systems: Unveiling the Role of Magajia in Customary Justice Systems in Auchi, Edo State, Nigeria. - Enaikele, M. D. (NIU Journal of Humanities, 2025)
Traditional justice systems in Africa are often perceived as exclusively patriarchal. However, the gendered authority of the Magajia in Auchi challenges this narrative. This study examines the role of the Magajia, a female traditional leader, in conflict resolution and moral guidance within Auchi’s customary justice systems. Using purposive sampling, thirty-six key informant interviews, focus group discussions, and participant observation at community court sessions were conducted. Findings reveal that the Magajia is usually an elderly woman appointed by senior women or traditional rulers to mediate disputes, upholds moral standards, and represents women’s interests. Though her judgments lack legal enforcement under the state law, but her influence within the community remains significant.  Therefore, institutionalizing the Magajia’s role and providing training in leadership, legal literacy, and digital skills could enhance her relevance in modern governance structures. Above all, the study underscores the need to recognize and empower gender-inclusive traditional justice systems in Nigeria. Keywords: Unveiling, The Magajia, Traditional Justice systems, Auchi, Edo State Nigeria.